Spatial patterns and determinants of knowledge on prevention of mother-to-child transmission of HIV in Ethiopia: a geographically weighted regression analysis - Angwach Abrham Asnake; Alemayehu Kasu Gebrehana; Yohannes Mekuria Negussie; Beminate Lemma Seifu; Hiwot Altaye Asebe; Bezawit Melak Fente; Meklit Melaku Bezie; Mamaru Melkam; Zufan Alamrie Asmare; Sintayehu Simie Tsega (BMC Pregnancy and Childbirth)
Abstract Background Prevention of Mother-to-Child Transmission (PMTCT) program has been a cornerstone in the fight against (Human immunodeficiency virus) HIV, aiming to reduce the transmission of HIV from mother to child during pregnancy, childbirth, and breastfeeding in Ethiopia. Geographic barriers, particularly in remote and underserved regions, significantly hinder access to healthcare facilities and essential programs. These challenges contribute to the suboptimal uptake of PMTCT services, leading to higher rates of vertical HIV transmission and exacerbating health inequities. Despite these, geographical variations in knowledge about PMTCT remain poorly understood, with limited efforts made to quantify the geographic heterogeneity in knowledge across Ethiopian regions. Therefore, this study aims to examine and explain the geographic variations in knowledge about PMTCT among Ethiopian mothers, using nationally representative data from the Ethiopian Demographic and Health Surveys (EDHS). Method This study utilized the 2016 EDHS dataset, which was cross-sectional by design. A weighted sample of 4,476 mothers was included. Spatial autocorrelation analysis was conducted to assess whether maternal care utilization followed patterns of dispersion, clustering, or random distribution. Hotspot analysis using the Getis-Ord Gi statistic, identified geographic concentrations of poor PMTCT knowledge. Additionally, Ordinary Least Squares (OLS) regression was employed to determine factors influencing geographic variation, while Geographically Weighted Regression (GWR) assessed the spatial variability in associations between PMTCT knowledge and selected predictor. Results Statistically significant hotspots of poor PMTCT (Prevention of Mother-to-Child Transmission of HIV) knowledge were identified in the Somali, Afar, Southwest Oromia, and Northeastern SNNPR regions. Spatial regression analysis revealed that geographical disparities in PMTCT knowledge were primarily influenced by wealth status, media access, employment status, and proximity to health facilities. Conclusion This study revealed significant geographic and sociodemographic disparities in PMTCT knowledge among Ethiopian women. Targeted strategies are needed to improve knowledge in low-performing regions, particularly in Somali and Afar, by leveraging media, improving access to education, and integrating PMTCT messages into maternal health services. These findings can inform policy makers and program designers aiming to achieve the elimination of mother-to-child HIV transmission in Ethiopia. Targeted community-based interventions, mass media campaigns, and integration of PMTCT education into maternal healthcare are essential, particularly in hotspot regions. Policymakers should prioritize resource allocation to improve health facility accessibility and reduce barriers related to distance and affordability. Strengthening education and digital health initiatives can further bridge knowledge gaps. Addressing these challenges will enhance PMTCT awareness, reduce mother-to-child HIV transmission, and improve maternal and child health outcomes nationwide.